The EU and its member-states: Institutional contrasts and their consequences - Vivien A. Schmidt (Max Planck Institute for the Study of Societies, 1999)
The EU is a supranational governance organization which is quasi-federal in institutional structure and quasi-pluralist in policymaking processes. As such, it has had a significant impact on all member-states' institutional structures, whether federal or unitary, and their policymaking processes, whether statist or corporatist. But it has had a greater impact on countries such as France and Britain, which are unitary and statist, than on a federal, corporatist country such as Germany, where there is better goodness of fit. The problems of democratic legitimacy, which occur not only at the EU level but also at the national level, are therefore again greater in France and in Britain than in Germany.
Keywords: 300